Mesenchymal Stem Cell-Macrophage Crosstalk and Maintenance of Inflammatory Microenvironment Homeostasis - Lu, Di; Xu, Yan; Liu, Qiuli; Zhang, Qi (Frontiers in Cell and Developmental Biology, 2021)
Macrophages are involved in almost every aspect of biological systems and include development, homeostasis and repair. Mesenchymal stem cells (MSCs) have good clinical application prospects due to their ability to regulate adaptive and innate immune cells, particularly macrophages, and they have been used successfully for many immune disorders, including inflammatory bowel disease (IBD), acute lung injury, and wound healing, which have been reported as macrophage-mediated disorders. In the present review, we focus on the interaction between MSCs and macrophages and summarize their methods of interaction and communication, such as cell-to-cell contact, soluble factor secretion, and organelle transfer. In addition, we discuss the roles of MSC-macrophage crosstalk in the development of disease and maintenance of homeostasis of inflammatory microenvironments. Finally, we provide optimal strategies for applications in immune-related disease treatments.